DISASTER RISK MANAGEMENT IN MALAYSIA: ISSUES AND CHALLENGES FROM THE PERSEPCTIVE OF AGENCIES - Omar Chong, Noraini; Kamarudin, Khairul Hisyam (PLANNING MALAYSIA, 2018)
Disaster is a major threat that could jeopardise the development of economic, social and physical elements of a nation as well as the well-being of its people. The damage and loss of property and life caused by disasters are overwhelming and least desired by any country. Review of literature as presented in this research indicated that by having a good disaster risk management (DRM) plan and well-coordinated efforts and commitment among related disaster management agencies at all levels and local stakeholders, would potentially lead to disaster risk reductions, increase preparedness and response, and reduction of damage to assets and loss of life. With a long list of agencies and aid bodies that are currently involved in various stages of DRM, putting the idea into reality has proven to be highly challenging particularly on establishing good coordination between agencies and with other stakeholders for a more effective DRM process. This paper identified three major issues and challenges in DRM in Malaysia, particularly from the perspective of agencies. These issues and challenges include (1) disaster management planning imbalanced between top-down and bottom-up approaches, (2) lack of coordination in disaster management cycle, with greater focus only on the disaster emergency response stage and, (3) lack of planning of long-term recovery (post-disaster) process, which resulted in low level community and stakeholders’ resilience to disasters.